2017
DOI: 10.25134/erjee.v6i1.775
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Patterns in English as Foreign Language Classroom at Lower Secondary Schools

Abstract: Interaction plays an important role in language learning process in classroom setting. This present study aims at investigating the patterns used in classroom interaction by English lower secondary teachers. Using qualitative approach, this study was carried out in eight lower secondary schools (SMP) in Jakarta. Moreover, twenty English language experienced teachers with three to thirty-six years of teaching experiences were recruited as participants. Interviews, classroom observations/recording and focus-grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
2
5
0
Order By: Relevance
“…The lower level the students were, the smaller the group setting had to be, she concluded. Classroom modes in the combination of individuals, pair and group activities are also reported by Behroozizad, Nambiar and Amir (2012), Nisa (2014), and Sundari, Rafli and Ridwan (2017).…”
Section: Table 3 Features Of Shared Intentionsupporting
confidence: 55%
“…The lower level the students were, the smaller the group setting had to be, she concluded. Classroom modes in the combination of individuals, pair and group activities are also reported by Behroozizad, Nambiar and Amir (2012), Nisa (2014), and Sundari, Rafli and Ridwan (2017).…”
Section: Table 3 Features Of Shared Intentionsupporting
confidence: 55%
“…To create a reciprocal relationship with the students, in IE2, she provided praise or encouragement intensively to respect their struggle in accomplishing the assignments. The significant aspect of EFL classroom interaction that should be considered by teachers is not only teaching and managing the classroom but also evoking the relationship to their students (Amatari, 2015;Sundari, 2017). Thus, it indicates that gives directions was also able to generate the students' engagement under the teacher's control.…”
Section: Criticizes Student Behaviormentioning
confidence: 99%
“…Different from findings of research done by Sundari et al (2017) which emphasized patterns of teacher and student interactions, this study further described how teachers and students interacted in the classroom. Interestingly, the results of the research showed the similarity of the results in which there were interactions between the English teacher and the students, both in a whole class and individually.…”
Section: Discussionmentioning
confidence: 66%
“…Many studies have analyzed student-teacher engagement during the English learning process. Sundari et al (2017) concluded that when interacting and communicating with the students in the classroom, teachers do not strictly follow the IRF structure. Regarding the interaction patterns in language classrooms, it was found that at least three modified IRF structures.…”
Section: Introductionmentioning
confidence: 99%